Экспертно-аналитический процесс выбора управляющих организационных воздействий с использованием корпоративного знания. Часть 1. Формальный анализ системы целей - Ильина, Е.П. (Проблеми програмування, 2017)
Работа посвящена моделям и методам поддержки экспертного выбора варианта управляющего воздействия, реализуемого организационными мероприятиями. В первой части представлена модель системы целей организации и методы анализа отношений эквивалентности, противоположности и достижимости целей. Такой анализ служит поддержке аналитической функции формирования контекста и рекомендаций для экспертно-аналитического процесса оценивания и выбора вариантов воздействия, который будет рассмотрен в следующей части статьи. Робота присвячена моделям та методам підтримки експертного вибору варіанта керуючої дії, яка реалізується організаційними заходами. В першій частині подано модель системи цілей організації та методи аналізу відношень еквівалентності, протилежності та достатності цілей. Такий аналіз здійснює підтримку аналітичної функції формування контексту та рекомендацій для експертно-аналітичного процесу, який розглядатиметься у наступній частині статті. Paper is devoted to the models and the methods of support for the special process of the alternative management action expert choice when the action has to be realized by organizational measures. Such the choice takes into account the influence of the action on the decidable problem situation and its probable negative aftereffects in organization activity field. In Part I the model of the organization goals is presented. This model includes such the types of goals as standard, planned, produced by stakeholders' interests and brought about the decisions made in organization ones. The goals included are both hard and soft ones. The properties of goals such as equivalence, opposition and accessibility are formalized by means the model proposed. The analysis of these properties that is realized under actual state of the decision field and goals field of organization is employed as important analytical support for the expert analytical choice process. It includes the functions of the context and recommendations forming for the action perspectivity expert evaluation that will be considered in the next part of this paper.